EFL Classroom Discourse; From the Perspective of Discourse Analysis and Conversation Analysis - Putri, Dian Mega (Universitas PGRI Sumatera Barat, 2018)
This research aims to analyze the EFL classroom discourse by investigating the terms of IRF (Initiation, Response, and Feedback) structures, turn taking, conversational repair and repetition. The subjects were two English teachers and their students from different schools SMKN 10 and SMA Adabiah Padang. The data was collected from classroom recording. The recordings were taken in one meeting for each teacher. There are four findings in this research. First, the discourse structure in EFL classroom is more complex than single IRF model which also includes the IRFR structure, the IR [I1R1 … (InRn)] F structure and the IR1F1R2F2 …RnFn structure. Second, students in EFL classroom rarely initiate the conversation, and usually take the turn by nomination. Third, it is found that repairs are frequently adopted by the teacher and students to cope with problems in speaking, hearing and understanding. Fourth, repetition frequently occurs in EFL classroom, and teachers usually use repetition to emphasize or guide students to complete utterance, and students usually repeat part or all teachers’ utterance to show their confirmation or doubts. In conclusion most of the interaction in the EFL classroom is from the teacher to the students, there is little student initiative and little student-student interaction.